From Memorizing to Internalizing: Tahfidz Extracurricular as a Model for Religious Character Education in Islamic Elementary Schools - Zaenol Fajri; Izzah Nur Laila (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the role of tahfidz extracurricular activities as a model for religious character education in Islamic elementary schools, focusing on the transformation from memorization to internalization. Methodology: This research employs a qualitative approach with a case study design conducted at MI Nurul Rahman Bondowoso. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing and verification. Data validity was ensured through source and technique triangulation. Main Findings: The findings reveal that structured and repetitive tahfidz activities contribute significantly to the development of students’ discipline, spiritual habits, and religious character. The internalization of values occurs gradually through memorization, repetition, habituation, and teacher modeling. The triangulation results indicate that structured activities, spirituality by repetition, and values by teacher modeling shape discipline. However, the internalization process varies among students, indicating certain limitations in achieving optimal outcomes. Novelty/Originality of this study: This study offers a conceptual contribution by positioning tahfidz extracurricular activities not merely as a memorization practice but as a systematic model for transforming memorization into internalized religious values. It highlights the “memorizing to internalizing” framework as a distinctive approach to religious character education in Islamic elementary schools.